The Role of Vitamin D Sufficiency in the Formation of Benign Diseases of the Mammary Glands - Inoyatova Nodira Miranvarovna; Asatova Munira Miryusupovna (International Journal on Integrated Education, 2022)
Benign diseases of the mammary glands, being a "mirror" of the hormonal background of a woman, create an unfavorable background for the development of breast cancer. A link has been established between the development of breast cancer and low blood levels of vitamin D in women. Given the above, the purpose of this study was to evaluate the status of vitamin D and the relationship with benign breast diseases. 111 women were examined, with the study of risk factors, with the determination of quantitative 25-OH vitamin D in blood serum and ultrasound examination of the mammary glands. All women were divided into two groups: group 1 - 78 women of reproductive age (22-49 years), group 2 - 33 women of menopausal age (50 years and older). The average age of group 1 was 37.8 years, group 2 - 54.9 years. 98.7% of women of reproductive age and 98% of postmenopausal women had vitamin D deficiency or insufficiency. The frequency of mastopathy according to ultrasound diagnostics was 61.5% in group 1 and 24.2% in group 2. In the group of women of reproductive age, benign diseases of the mammary glands were three times more common than in the group of older women, apparently, this is due to the presence of a hyper estrogen state. There are a lot of risk factors for the development of dyshormonal diseases of the mammary glands, vitamin D deficiency is one of them.